(3JYdjbI Ydi cJGH GdecGSHs - (3GdgePGfj, GdfLaj, CZG QVG Hf eMeO gGOj, J (B1322(3g`s ((3eMeO UGOb Hf MSf HMQ GdYdhes)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi NjQ Ndbg eMeO hYJQJg GdWGgQjf(B... (3cJGH GdHjY bHd GdTQhY aj GdebUhO(B...s
(3BNQgG (B:s
(3GdJUQa aj GdeHjY cGTa Yf GdQVG HGdYjhH (B... (3dG jNdh ef fXQ hdh HYO GdYde HGdYjf CjVG dh de jYde YOe LhGR GdCQT aJCeds
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B720s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B720s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis